Business plan for a three or four star hotel in Baikal - Osetrova, Maria; Cook, Gina, 1970-; Lisa, Aleš, 1956-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2011)
The goal of this thesis is to analyze the business environment in the Baikal region for the hospitality management industry, specifically for a 3-4 star hotel. The topic is very current and under discussion now because the Russian state authorities would like to create a place attractive for tourism in Baikal and there is currently an economically favorable environment for the hotel industry. There is also government support in promotion of the region for tourism and cooperation with other government or non-government association or organization for development tourism there.
Vedoucí práce: Gina Cook
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2011
Rok obhajoby 2011
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses